2009
DOI: 10.2807/ese.14.47.19423-en
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and other STI in men who have sex with men – a continuous challenge for public health

Abstract: Citation style for this article: van de Laar MJ. HIV/AIDS and other STI in men who have sex with men -a continuous challenge for public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(34 reference statements)
0
9
0
1
Order By: Relevance
“…In 2009, 9,023 newly diagnosed HIV infections were reported among this population in Europe, which accounts for 35% of all HIV diagnoses in that year (European Centre for Disease Prevention and Control ECDC/World Health Organisation WHO -Regional Office for Europe, 2010;Likatavi ius et al, 2008). Moreover, in this specific population, a high level of risk behaviours associated with an increasing incidence of other Sexually Transmitted Infections (STI) clearly show the need for specific and targeted prevention campaigns (Dodds et al, 2005;Van de Laar et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In 2009, 9,023 newly diagnosed HIV infections were reported among this population in Europe, which accounts for 35% of all HIV diagnoses in that year (European Centre for Disease Prevention and Control ECDC/World Health Organisation WHO -Regional Office for Europe, 2010;Likatavi ius et al, 2008). Moreover, in this specific population, a high level of risk behaviours associated with an increasing incidence of other Sexually Transmitted Infections (STI) clearly show the need for specific and targeted prevention campaigns (Dodds et al, 2005;Van de Laar et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…[8] Syphilis infection may drive people to seek care earlier by causing a visible lesion requiring treatment, and STI care-seeking increases the likelihood of concomitant HIV testing. [29,30] Untreated syphilis infection has also been shown to increase susceptibility to acquiring HIV and may have been a major risk factor for infection among these participants. [30] Other studies have shown an association between recent syphilis infection and HIV serostatus awareness.…”
Section: Discussionmentioning
confidence: 99%
“…This number is about one fifth (19%) smaller than 3.17 million (2.9-3.4 million) people who were newly infected in 1999, and more than one fifth (21%) smaller than in 1997, when annual new infections peaked (1). There is a strong evidence of resurgent HIV epidemics among men who have sex with men (MSM) in North America and in Western Europe and this group continues to represent a population at high risk of HIV infection (2,3). Data from 23 western countries show that the annual number of men who have sex with men diagnosed with HIV infection rose by 86% between 2000 and 2006 (4).…”
Section: Introductionmentioning
confidence: 99%